PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Mahasiswa/i Unisbank Semarang pengguna Smartphone Samsung) - Ayu Krisnintliana, 14.05.51.0236; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2018)
The purpose of this study to determine whether there is influence of product quality, brand image and price perception of Samsung Smartphone purchase decision. The result of the analysis is the quality of the product has no effect and significant so that all changes - changes that occur in the variable purchase decision is not influenced by product quality veriabel. Furthermore, the brand image does not have a positive and significant impact so that any changes that occur in the purchase decision variable are not affected by the brand image variable. While the perception of the price has a positive and significant effect so it can be stated that the perception of the price can affect the purchase decision. It is known that the value of Adjusted R Square is 0,535 which means that 53,5% of variation of purchasing decision can be explained by product quality variable, brand imageand price perception.Keywords: product quality, brand image, price perception and purchase decision